Neoadjuvant chemotherapy for early breast cancer - Krug, David; Loibl, Sibylle (The lancet. Oncology, 2018)
We congratulate the Early Breast Cancer Trialists' Collaborative Group (EBCTCG) on - their important meta-analysis.1 Neoadjuvant chemotherapy (NACT) has become an important - tool and strategy for patients with breast cancer. Although NACT was traditionally - used in patients with locally advanced breast cancer, with the aim of downstaging - and achieving operability, monitoring treatment response for prognostic purposes and - for risk stratification has become routine in current practice.